Organisasi Mahasiswa Melayu Pattani di Lampung: Kontinuitas, Perubahan dan Tantangan Tahun 2009-2024 - Husen Ismae; Aan Budianto; Agus Mahfudin Setiawan; Wahyu Iryana; Ahmad Basyori; Uswatun Hasanah (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
Since their arrival in Indonesia, Pattani Malay students have played a pivotal role in fostering solidarity, strengthening Islamic identity, and expanding intellectual networks. One significant outcome of this dynamic was the establishment of the Association of Pattani Malay Students in Indonesia in Lampung, in 2009. Despite its importance, research on this organization remains limited, with most studies focusing on the broader history of the Pattani student diaspora in Indonesia rather than examining the continuity, transformation, and challenges of PMMPI in the specific local context of Lampung. This study adopts the historical method, comprising four stages: heuristics, source criticism, interpretation, and historiography. Data were collected from organizational documents, activity archives, relevant literature, and interviews with core leaders spanning the period from 2012 to 2024. The findings indicate that PMMPI has sustained its continuity through systematic cadre regeneration and the affirmation of Islamic values as the foundation of identity. Organizational changes have occurred in terms of structure, nomenclature, and strategic orientation, demonstrating adaptability to social, political, and academic dynamics. At the same time, the organization has faced persistent challenges, including language barriers, social integration, and global crises such as the Covid-19 pandemic. Overall, the study underscores that PMMPI functions not merely as a student association, but also as an agent of identity formation, solidarity, and adaptation for Pattani students in Indonesia. The implications highlight the need for further exploration of the role of diaspora organizations in reinforcing religious, national, and academic ties within the context of globalization.